PENGARUH LITERASI DIGITAL TERHADAP KINERJA AKADEMIK DAN NIAT KEWIRAUSAHAAN DI KALANGAN MAHASISWA D3 ADMINISTRASI BISNIS DI INDONESIA - Taufik Akbar; Hafnizah Amir (Jurnal Manajemen, Ekonomi dan Akutansi (JUMEA), 2024)
This study examines digital literacy's impact on academic performance and entrepreneurial intentions among students of the D3 Business Administration program in Indonesia. In an increasingly digital era, digital literacy has become an essential skill that can influence various aspects of students' lives, including academic achievement and the inclination to engage in entrepreneurship. This research employs a quantitative approach using surveys as the data collection method. Data were collected from 100 students of the D3 Business Administration program at Politeknik Negeri Jakarta. Multiple linear regression analysis was conducted to test the relationship between digital literacy and academic performance and entrepreneurial intentions. The results indicate that digital literacy has a significant positive effect on students' academic performance and entrepreneurial intentions. The implications of these findings underscore the importance of integrating digital literacy into higher education curricula to enhance academic performance and foster entrepreneurial intentions among students.